2004
DOI: 10.1099/vir.0.79958-0
|View full text |Cite
|
Sign up to set email alerts
|

Active NF-κB signalling is a prerequisite for influenza virus infection

Abstract: Influenza virus still poses a major threat to human health. Despite widespread vaccination programmes and the development of drugs targeting essential viral proteins, the extremely high mutation rate of influenza virus still leads to the emergence of new pathogenic virus strains. Therefore, it has been suggested that cellular cofactors that are essential for influenza virus infection might be better targets for antiviral therapy. It has previously been reported that influenza virus efficiently infects Epstein-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
152
1
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(162 citation statements)
references
References 39 publications
(37 reference statements)
4
152
1
5
Order By: Relevance
“…We and others could show that influenza A virus infection is associated with expression of NF-Bdependent gene products such as proinflammatory cytokines in cell culture (6, 53, 56 -58) and in vivo models (59 -61). Work from our group and others revealed that influenza A virus replication induces and depends on activation of NF-B (31,42,62,63), most presumably by subsequent activation of caspases that enhance the passive release of viral ribonucleoproteins from the nucleus in late phases of viral replication. During preparation of this manuscript, Kumar et al (64) additionally claimed that NF-B signaling is important for the synthesis of viral RNA in influenza virus-infected cells.…”
Section: Discussionmentioning
confidence: 99%
“…We and others could show that influenza A virus infection is associated with expression of NF-Bdependent gene products such as proinflammatory cytokines in cell culture (6, 53, 56 -58) and in vivo models (59 -61). Work from our group and others revealed that influenza A virus replication induces and depends on activation of NF-B (31,42,62,63), most presumably by subsequent activation of caspases that enhance the passive release of viral ribonucleoproteins from the nucleus in late phases of viral replication. During preparation of this manuscript, Kumar et al (64) additionally claimed that NF-B signaling is important for the synthesis of viral RNA in influenza virus-infected cells.…”
Section: Discussionmentioning
confidence: 99%
“…The susceptibility of cells to influenza A virus is known to depend on the level of NF-B activation (22,23). Normally, IB␣ silences NF-B activation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, active NF-B signaling has been demonstrated to be a prerequisite for efficient influenza A virus infection of human cells (22,23). The inhibitory subunit, IB␣, maintains NF-B in an inactive state and is degraded in the course of NF-B activation.…”
Section: Simultaneous Application Of Par 2 -Cap and Ifn-␥ Reduces Ib␣mentioning
confidence: 99%
“…They have multiple signal effects, one of them being activation of the transcription factor NF-kappaB (54Á56). But NF-kappaB has been reported to stimulate replication of the influenza virus and to be necessary for its replication (57,58). More replication of the influenza virus (causing enhanced viral load) must in turn be expected to lead to enhanced stimulation of the expression and secretion of various cytokines, including TNF-a.…”
Section: Evolution Of Virulence Properties In Influenza Virusesmentioning
confidence: 99%